The Predictive Roles of Prosocial and Aggressive Behaviours, and Socioeconomic Status on Perceived Classroom Climate in 4th-grade Children - Bıkmazoğlu, Ogün (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Classrooms are one of the important socializing venues for children. It is important to understand the factors that affect perceived classroom climate because children spend more time at school compared to home. Outcomes of classroom climate includes attendance records, surface vs. deeper learning, grades of students, learning motivations, level of bullying and conflict, level of prosocial behaviours and cooperation among peers. That’s why it is important to be aware of the factors that affect perceived classroom climate in order to decrease negative behaviours (i.e. bullying and conflict) and promote positive behaviours (i.e. prosocial behaviours). Therefore, the current study aimed to examine; (a) aggressive and prosocial behaviours, (b) socioeconomic status of parents (parental level of income and parental education level), (c) students’ perceptions of the classroom climate. The sample consisted of 152 (81 male, 71 female) Turkish speaking students who completed self-report measures including; demographic questionnaire, Aggressive and Prosocial Behaviours Questionnaire and Student’s Perceptions of the Classroom Environment Scale. Results revealed that there was a positive correlation between combined prosocial behaviours and perceived positive classroom climate. Whereas, there was a negative correlation between combined aggressive behaviours and perceived positive classroom climate. Also, parental SES, combined prosocial behaviours and combined aggressive behaviours mediate and moderate the link of perceived positive classroom climate. Keywords: Parental Socioeconomic Status, Aggressive and Prosocial Behaviours, Perceived Positive Classroom Climate.

ÖZ: Bireylerin yakın çevresi motivasyonlarında ve davranışlarında önemli bir rol oynar. Sınıflar çocuklar için önemli sosyalleşme alanlarından biridir. Algılanan sınıf iklimini etkileyen faktörleri anlamak önemlidir, çünkü çocuklar okulda ve sınıflarında evlerine göre daha fazla zaman geçirirler. Sınıf iklimi, öğrencilerin derse katılım düzeyini, yüzeye göre daha derin öğrenmeyi, öğrencilerin notlarını, öğrenme motivasyonlarını, zorbalık ve çatışma düzeyini, olumlu sosyal davranışların seviyesini ve akranlar arasındaki işbirliğini içerir. Bu nedenle olumsuz davranışları (yani zorbalık ve çatışma) azaltmak ve olumlu davranışları (yani olumlu sosyal davranışlar) teşvik etmek için algılanan sınıf iklimini etkileyen faktörlerin farkında olmak önemlidir. Bu nedenle, bu çalışmanın incelediği noktalar; (a) agresif ve olumlu sosyal davranışlar, (b) ebeveynlerin sosyoekonomik durumu (ebeveyn gelir düzeyi ve ebeveyn eğitimi düzeyi), (c) öğrencilerin sınıf iklimine ilişkin algıları, olarak belirlenmiştir. Araştırmaya, Türkçe konuşan, 152 (81 erkek, 71 kız) ilkokul öğrencisi katılmıştır. Demografik Anket, Olumlu Sosyal ve Saldırgan Davranışlar Ölçeği ve Sınıfın Sosyal Çevresini Algılama Ölçeği katılımcılar tarafından doldurulmuştur. Sonuçlar, olumlu sosyal davranışlar ve algılanan olumlu sınıf iklimi arasında pozitif bir korelasyon olduğunu ortaya koymuştur. Buna karşılık, agresif davranışlar ile algılanan olumlu sınıf iklimi arasında negatif bir korelasyon olduğu ortaya çıkmıştır. Ayrıca, ailenin sosyo ekonomik durumu, olumlu sosyal davranışlar ve agresif davranışlar, algılanan olumlu sınıf iklimi arasındaki bağlantıya aracılık ettiği ve bu ilişkiyi yönlendirdiği ortaya çıkmıştır.
Master of Science in General Psychology. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2020. Supervisor: Supervisor: Assoc. Prof. Dr. Fatih Bayraktar.
Keywords: Psychology; General Psychology; Aggression--Psychology--Emotions; Parental Socioeconomic Status; Aggressive and Prosocial Behaviours; Perceived Positive Classroom Climate